The Fairness of Organization’s Performance Appraisal Social Capital and The Impact Toward Affective Commitment - Tjahjono, Heru Kurnianto (UI Scholars Hub, 2015)
This experimental study aims to examine the impact of distributive and procedural justice towards affective commitment in every context or situation that is configurational. The meta-analysis, concluded by Hartman, Yale, and Galle (1999), explained that researches on fairness in general was conducted in the context of unfairness. This particular study examined various situations to form a configuration of distributive justice, procedural justice, and subjective perspective of social capital as moderating variable. This study involved 268 subjects in one class relation to performance appraisal's policy. The findings show that both distributive and procedural justice are vital predictors. Similarly, the configuration of these variables play a role in explaining affective commitment. Another important finding is that social capital, as a subjective perspective, plays a significant role in explaining affective commitment.